MAKING BOOK ON APPLICATIONS OFFICE ADDRESS CORRUPTION ERADICATION COMMISSION (KPK) USING MICROSOFT VISUAL BASIC 6.0 - Wuri Pancawati; Yulina, SKom, MMSI Yulina, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Use the address book as a place to search for those addresses are often used, but when the data sought is so much we need a long time to find the address in question and hence reducing the efficiency of work of the author. With this application, making this book the author hopes to address the mentioned problems can be overcome. This program can also print directly address book with addresses for outgoing mail in question.